Analisis Proses Clearance In/Out Kapal Cargo Lokal Dengan Sistem Inapornet Pada Pt Samudera Indonesia Pelabuhan Dwikora Pontianak - Yudika, Ruby; Firjatullah, Faisal Ary; Qamaruddin, Qamaruddin (Peneliti.net, 2024)
This research was carried out at PT Samudera Indonesia Pontianak branch with the aim of studying the in/out clearance process using the inapornet system, the obstacles being faced and the efforts to overcome them. The research approach is descriptive qualitative. Data was collected through observation, documentation techniques and literature study. Based on the research results, it can be concluded that the obstacles that occur were that the Inapornet system experienced an error or is down, there was no supporting feature available for uploading documents or files, and there was no connection with the VTS (Vessel Traffic Service) agency or VTS service. Efforts that need to be made to overcome these obstacles are to immediately contact the relevant agency regarding the problem. In the cases where supporting features are not yet available on Inapornet, the agent can immediately collect the ship's documents after the ship has docked, and if the condition was not yet connected to the VTS agency, the agent immediately contacts one of them, the agency was to send requests for VTS services using social media so as to speed up the publication of the document to be uploaded in the Inapornet system.